A large-area continuous MOF membrane and its preparation method and application
2D Zr-BTB nanosheets were constructed and modified by solvothermal method, and large-area continuous MOF membranes were prepared by scraping coating, which solved the problems of small area, fragility, and weighed the permeability and selectivity of the MOF membrane in the prior art, and achieved efficient lithium ion sieving effect.
Patent Information
- Application Number
- CN202510065252.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-16
AI Technical Summary
It is difficult to prepare large-area continuous MOF membranes in the prior art, and there are problems such as fragility and pulverization. Traditional non-porous two-dimensional layered nanosheets hinder the increase of permeability and selectivity, and the trade-off between permeability and selectivity cannot be avoided.
2D Zr-BTB nanosheets were constructed from bottom to top using zirconium tetrachloride and 1,3,5-tris(4-carboxyphenyl)benzene as raw materials, and sulfonate functional groups were modified by syringe reagent during the synthesis process, and large-area continuous MOF membranes were quickly self-assembled by scraping coating.
The preparation of a large-area continuous MOF film is achieved, with excellent lithium ion selectivity and permeability, and overcomes the problem of difficult film formation and twisted two-dimensional film transmission paths in traditional MOF materials.
Smart Images

Figure CN119455707B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane material preparation and membrane separation, and specifically relates to a large-area continuous MOF membrane and a preparation method and application thereof. Background Art
[0002] With the rapid development of human society, the problem of resource shortage is becoming increasingly prominent. Separation membranes have broad application prospects in the fields of ion / molecule separation, seawater desalination, catalysis, energy storage and conversion due to their unique structure and mass transfer characteristics. Among them, two-dimensional layered membranes formed by stacking atomic-thick nanosheets are ideal materials for separation membranes.
[0003] Existing nanosheets include graphene and its derivatives, MoS2, and two-dimensional transition metal carbonitrides (MXene), etc. However, these traditional non-porous two-dimensional layered nanosheets force ions / molecules to be transported along highly curved nanochannels within the plane, which to some extent hinders the improvement of permeation flux and cannot avoid the trade-off between permeability and selectivity.
[0004] As a type of porous two-dimensional layered nanosheets, two-dimensional metal-organic frameworks (MOFs) allow ions / molecules to pass through the nanosheets directly, rather than only along the plane, thanks to the inherent pores on the two-dimensional MOF nanosheets, which effectively reduces the length and tortuosity of the transmission path. Although the porous properties of MOF materials can provide a large number of transmission paths, which is beneficial to improving the permeation flux of the film, it is difficult to prepare large-area continuous MOF membranes, and there are problems such as fragility and easy pulverization.
[0005] Common methods for preparing MOF membranes include interfacial synthesis, liquid phase epitaxy, impregnation, atomic layer deposition, chemical vapor deposition and vacuum filtration. However, the MOFs prepared by these methods are limited in size, the operation process is complicated, and the requirements for equipment and operating environment are high.
[0006] In the article "Two-dimensional sulfonate-functionalized metal–organicframework membranes for efficient lithium-ion sieving" published in Volume 24, Issue 9 of Nano Express, PSS polymer was added to the MOF dispersion, and a composite membrane was formed on an anodic aluminum oxide (AAO) substrate by vacuum filtration to improve the stability of the MOF membrane. However, the use of PSS polymer additives will affect the storage time of the MOF dispersion and cause sedimentation. In addition, the AAO substrate is expensive and difficult to produce on a large scale. It is also brittle and prone to damage during the transfer process. During the film drying process, the rigid AAO substrate often warps at the edges or even falls off the substrate because it cannot match the slight deformation of the solution during film formation and shrinkage. Therefore, the film formation on the AAO substrate requires careful control of the film drying rate and drying conditions, and the membrane area prepared by this method is small, with a diameter of 1.5 cm. Summary of the invention
[0007] The purpose of the present invention is to address the above-mentioned problems in the prior art and to propose a large-area continuous MOF membrane and a preparation method and application thereof.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention is to provide a method for preparing a large-area continuous MOF film, comprising the following steps:
[0010] S1: dissolving zirconium tetrachloride and 1,3,5-tri(4-carboxyphenyl)benzene in N,N-dimethylformamide, then adding formic acid and water, sealing the obtained mixed solution, placing it in an oven for heat preservation, then adding the sulfonation reagent, refluxing for a period of time and then standing, and then centrifugally washing with ultrapure water to obtain a uniform dispersion;
[0011] S2: Wash the substrate in ethanol and deionized water respectively for later use;
[0012] S3: Fix the substrate on a doctor blade and spread the prepared dispersion on the surface of the substrate by doctor blade, and obtain a MOF film after drying;
[0013] S4: Transfer the MOF film to a vacuum oven to further stabilize the structure.
[0014] The present invention is further configured such that, in step S1, the mass ratio of zirconium tetrachloride to 1,3,5-tris(4-carboxyphenyl)benzene is 1:1 to 1:1.5.
[0015] The present invention is further configured such that, in step S1, in the mixed solution, the mass fraction of formic acid is 10% to 16%, and the mass fraction of water is 8% to 15%.
[0016] The present invention is further configured such that, in step S1, the sulfonation reagent is p-sulfobenzoic acid or sodium 5-sulfoisophthalic acid, preferably p-sulfobenzoic acid.
[0017] The present invention is further configured such that, in step S1, the molar ratio of the sulfonating agent to zirconium tetrachloride is 1:1 to 13:1, preferably 6:1 to 13:1.
[0018] The present invention is further configured such that, in step S1, the reflux temperature is 70-90°C, and the reflux time is 8-12h.
[0019] The present invention is further configured such that, in step S2, the substrate is selected from one of a polystyrene substrate, a glass fiber substrate and a polyacrylonitrile substrate, preferably a PAN substrate.
[0020] The present invention is further configured such that, in step S3, the drying temperature is 110-130°C, and the drying time is 1-3 hours.
[0021] The present invention is further configured such that, in step S4, the drying temperature of the vacuum oven is 80-120° C., and the drying time is 8-12 hours.
[0022] The second aspect of the present invention is to provide a large-area continuous MOF membrane prepared by the above preparation method.
[0023] The third aspect of the present invention is to provide the application of the large-area continuous MOF membrane prepared by the above preparation method in lithium ion screening.
[0024] The beneficial effects of the present invention are as follows:
[0025] (1) The present invention can conveniently and quickly prepare two-dimensional MOF nanosheets by solvothermal method, and can quickly self-assemble to prepare large-area continuous MOF films by scraping method. The area of the MOF film can reach several hundred square centimeters, which is determined by the area of the substrate and the accommodation area of the scraping equipment. The method can form large-area continuous MOF films on a variety of substrates in a short time at room temperature, has low requirements on instruments and equipment, is simple in operation, and has mild conditions, which is conducive to large-scale promotion and application.
[0026] (2) The present invention adopts a solvothermal method to construct 2D Zr-BTB nanosheets from bottom to top using zirconium tetrachloride (ZrCl4) and 1,3,5-tri(4-carboxyphenyl)benzene (BTB) as raw materials. Subsequently, during the synthesis process, a sulfonated reagent is used to directly modify the metal cluster sites with sulfonic acid functional groups. The resulting MOF dispersion is uniform and stable, has a long shelf life, and is conducive to film formation. The MOF membrane prepared by the doctor blade method exhibits excellent lithium ion selectivity and permeability under the dual regulation of size effect and affinity effect of sulfonic acid groups.
[0027] (3) The two-dimensional MOF membrane prepared by the present invention combines the advantages of two-dimensional materials and MOF materials, overcomes the defect that traditional MOF materials are difficult to form membranes, and makes up for the shortcomings of traditional two-dimensional membranes that the transmission path is tortuous and the permeation rate is difficult to improve. The intralayer pores of the nanosheets and the interlayer spacing of the layered membrane can both serve as entrances for ion transmission, providing a dual path for ion transmission within the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the bottom-up construction of 2D Zr-BTB-S nanosheets.
[0029] Figure 2 It is a comparison chart of the stability test of the dispersion of Example 1 and Comparative Example 1.
[0030] Figure 3 is the TEM image of 2D Zr-BTB-S nanosheets.
[0031] Figure 4 This is an optical picture of the large-area MOF film on the PAN substrate prepared in Example 2.
[0032] Figure 5 is a SEM image of the large-area MOF film on the PAN substrate prepared in Example 2.
[0033] Figure 6 It is a structural schematic diagram of the H-type test mold. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described clearly and in detail below by specific embodiments in conjunction with the accompanying drawings. It should be understood that the following embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Other embodiments obtained by ordinary technicians in this field without creative work should be included in the protection scope of the present invention.
[0035] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be purchased through commercial channels.
[0036] like Figure 1 As shown, the present invention adopts a solvothermal method, with zirconium tetrachloride (ZrCl4) and 1,3,5-tri(4-carboxyphenyl)benzene (BTB) as raw materials, to construct 2D Zr-BTB nanosheets from bottom to top, and then uses a sulfonation reagent to functionalize the 2D Zr-BTB nanosheets to obtain 2D Zr-BTB-S nanosheets, that is, during the synthesis process, sulfonic acid functional groups are directly modified on the metal cluster sites, and a large-area continuous two-dimensional MOF film is prepared by a scraping method.
[0037] Example 1
[0038] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL N,N-dimethylformamide (DMF), and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours, and then 0.525 g of p-sulfobenzoic acid was added, refluxed at 90 °C for 12 hours, and then allowed to stand for 12 hours. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet (MOF) dispersion was obtained.
[0039] Comparative Example 1
[0040] According to the synthesis of 2D Zr-BTB nanosheets and the synthesis of 2D Zr-BTB-PSS nanosheets (S2) in the article "Two-dimensional sulfonate-functionalized metal–organicframework membranes for efficient lithium-ion sieving" published in Nano Letters Vol. 24, No. 9, a 2D Zr-BTB-PSS nanosheet (MOF) dispersion was prepared.
[0041] The sulfonic acid functionalized MOF dispersions prepared in Example 1 and Comparative Example 1 were stored at room temperature and pressure for one week. Figure 2 As shown, the dispersion liquid with added polymer in Comparative Example 1 has obvious sedimentation, which makes it difficult to store for a long time, increasing the use cost, while the dispersion liquid prepared in Example 1 is still uniform and stable.
[0042] Example 2
[0043] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL of DMF, and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours. It was washed with DMF and ultrapure water (5000 rpm, 5 min), and then 0.525 g of p-sulfobenzoic acid was added. It was refluxed at 90 °C for 12 h and then allowed to stand for 12 h. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained, and its TEM image is shown in the figure. Figure 3 As shown in the figure, it can be concluded that the lateral size of the nanosheet is about 300nm, and the obvious lattice fringes indicate that it has good crystallinity.
[0044] The polyacrylonitrile (PAN) substrate was washed in ethanol and deionized water for 10 min respectively and then set aside. The PAN substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a 120 °C vacuum oven for 8 h for further drying. The optical image and SEM image of the obtained MOF film are shown in Figure 2. Figure 4-Figure 5 As shown, Figure 4 The MOF shown has an area of 15 cm*21 cm, consisting of Figure 5 It can be concluded that the surface of the prepared MOF membrane is smooth and has no obvious defects.
[0045] Example 3
[0046] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.1 g) were dissolved in 50 mL DMF, and then formic acid (6.5 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 24 hours. It was washed with DMF and ultrapure water (5000 rpm, 5 min), and then 0.105 g of p-sulfobenzoic acid was added, refluxed at 70 °C for 8 h, and then allowed to stand for 12 h. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained.
[0047] The PAN substrate was washed in ethanol and deionized water for 10 min respectively and then used. The PAN substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h for further drying.
[0048] Example 4
[0049] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.15 g) were dissolved in 50 mL DMF, and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours. It was washed with DMF and ultrapure water (5000 rpm, 5 min), and then 1.05 g of p-sulfobenzoic acid was added, refluxed at 90 °C for 12 h, and then allowed to stand for 12 h. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained.
[0050] The PAN substrate was washed in ethanol and deionized water for 10 min respectively and then used. The PAN substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h for further drying.
[0051] Example 5
[0052] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL DMF, and then formic acid (6.5 g) and water (9 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 12 hours, then washed with DMF and ultrapure water in sequence, and then 0.525 g of sodium 5-sulfonate of isophthalic acid was added, refluxed at 90 °C for 12 hours, and then allowed to stand for 12 hours. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained.
[0053] The PAN substrate was washed in ethanol and deionized water for 10 min respectively and then used. The PAN substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h for further drying.
[0054] Example 6
[0055] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL DMF, and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours, and then 0.525 g of p-sulfobenzoic acid was added. After reflux at 90 °C for 12 hours, it was allowed to stand for 12 hours. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained.
[0056] The polystyrene substrate was washed in ethanol and deionized water for 10 min respectively and then set aside. The polystyrene substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h to further stabilize the structure.
[0057] Example 7
[0058] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL DMF, and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours, and then 0.525 g of p-sulfobenzoic acid was added. After reflux at 90 °C for 12 hours, it was allowed to stand for 12 hours. After centrifugal washing with ultrapure water (5000 rpm, 5 min) five times, a uniform 2D Zr-BTB-S nanosheet dispersion was obtained.
[0059] The glass fiber substrate was washed in ethanol and deionized water for 10 min respectively and then put into use. The glass fiber substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h to further stabilize the structure.
[0060] Comparative Example 2
[0061] Comparative Example 2 is substantially the same as Example 2, except that p-sulfobenzoic acid is not added to the dispersion, specifically:
[0062] Zirconium tetrachloride (0.1 g) and 1,3,5-tri(4-carboxyphenyl)benzene (0.125 g) were dissolved in 50 mL DMF, and then formic acid (9.6 g) and water (6 mL) were added to prepare a mixed solution. The mixed solution was sealed and placed in an oven at 120 °C for 2 hours, and then centrifuged and washed with DMF and ultrapure water (5000 rpm, 5 min) five times to obtain a 2D Zr-BTB nanosheet dispersion.
[0063] The PAN substrate was washed in ethanol and deionized water for 10 min respectively and then used. The PAN substrate was fixed on a doctor blade and the prepared dispersion was spread on the substrate surface. The MOF film was obtained after drying for 30 min. Subsequently, the MOF film was transferred to a vacuum oven at 120 °C for 8 h for further drying.
[0064] The MOF membranes prepared in Examples 2 to 7 and Comparative Example 2 were clamped in Figure 6In the H-type test mold shown, the following permeability test was carried out.
[0065] Test 1
[0066] The raw liquid and permeate on both sides of the MOF membrane were equal volumes of 100 mM LiCl solution and ultrapure water, respectively. The conductivity of the permeate was monitored regularly and converted into ion concentration. Finally, the lithium ion permeation rate was calculated by the following formula (1). The results are shown in Table 1.
[0067] Ion permeation rate J s (mol·m -2 h -1 ):
[0068] (1)
[0069] Where C is the ion concentration of the permeate side (mol / L), V is the volume (L), and A is the effective test membrane area (m 2 ), Δt is the penetration time (h).
[0070] Test 2
[0071] The raw liquid and permeate on both sides of the MOF membrane are equal volumes of 100 mM mixed solution (equimolar concentrations of LiCl and KCl, or equimolar concentrations of LiCl and MgCl2) and ultrapure water, respectively. The ion concentration on one side of the permeate is monitored regularly. + / K + , Li + / Mg 2+ The selectivity factors are shown in Table 1.
[0072] Ion Selectivity Factor:
[0073] (2)
[0074] Among them, J x and J y is the ion permeation rate calculated by the above formula (1), x is Li + , y is K + or Mg 2+ .
[0075] Table 1
[0076]
[0077] From the results in Table 1, it can be seen that the MOF membrane modified with sulfonic acid functional groups prepared in the present invention has a higher lithium ion permeation rate and exhibits a good interception effect on both magnesium ions and potassium ions.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a large-area continuous MOF membrane, characterized in that: The following steps are involved: S1: dissolving zirconium tetrachloride and 1,3,5-tri(4-carboxyphenyl)benzene in a solvent N,N-dimethylformamide, then adding formic acid and water, sealing the obtained mixed solution, placing it in an oven for heat preservation, then adding a sulfonation reagent, refluxing for a period of time and then standing, and then centrifugally washing with ultrapure water to obtain a uniform dispersion; S2: Wash the substrate in ethanol and deionized water respectively for later use; S3: Fix the substrate on a doctor blade and spread the prepared dispersion on the surface of the substrate by doctor blade, and obtain a MOF film after drying; S4: Transfer the MOF film to a vacuum oven to further stabilize the structure; In step S1, the sulfonating agent is p-sulfobenzoic acid or sodium 5-sulfoisophthalic acid.
2. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S1, the mass ratio of zirconium tetrachloride to 1,3,5-tris(4-carboxyphenyl)benzene is 1:1 to 1:1.5; In the mixed solution, the mass fraction of formic acid is 10% to 16%, and the mass fraction of water is 8% to 15%.
3. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S1, the molar ratio of the sulfonating agent to zirconium tetrachloride is 1:1 to 13:
1.
4. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S1, the reflux temperature is 70-90°C, and the reflux time is 8-12 hours.
5. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S2, the substrate is selected from one of a polystyrene substrate, a glass fiber substrate and a polyacrylonitrile substrate.
6. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S3, the drying temperature is 110-130°C, and the drying time is 1-3 hours.
7. The method for preparing a large-area continuous MOF film according to claim 1, characterized in that: In step S4, the drying temperature of the vacuum oven is 80-120° C., and the drying time is 8-12 hours.
8. A large-area continuous MOF membrane, characterized in that: The large-area continuous MOF membrane is prepared by the method for preparing a large-area continuous MOF membrane according to any one of claims 1 to 7.
9. An application of a large-area continuous MOF membrane, characterized in that: The large-area continuous MOF membrane is prepared by the method for preparing a large-area continuous MOF membrane according to any one of claims 1 to 7, and is used for lithium ion screening.
Citation Information
Patent Citations
Method for synthesizing metal organic framework material macromolecule polymer film
CN110256706A